PERAN PEMERINTAH MELALUI DINAS KESEHATAN KABUPATEN SUMBAWA BARAT DALAM MENYOSIALISASIKAN BAHAYA MERKURI BAGI KESEHATAN DI KECAMATAN BRANG REA - Yusmawati, Yusmawati; Permana, Restiawan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2019)
The number of unlicensed (illegal) community gold miners occurs in West Sumbawa Regency, especially in Brang Rea District. This results in river water being polluted with mercury by the mining waste. Creation of public health problems there. The formulation of the problem in this study is the role of the government through the West Sumbawa Regency Health Office in socializing the dangers of mercury for public health in the District of Brang Rea? The purpose of this study was to study how the government through the West Sumbawa District Health Office in socializing the dangers of mercury for public health in the District of Brang Rea. The approach used in this research is qualitative. While this type of research uses descriptive methods. Health communication requires methods and media so that messages can be conveyed properly. Face to face communication methods conducted by health workers in the form of health education with messages containing mercury hazards to health. In addition to face-to-face communication methods, health communication media such as posters are also needed. The poster was chosen by the Brang Rea Health Center in its health communication activities on the grounds that the poster is suitable to be used as a follow up to a message that was delivered some time ago. Thus the poster aims to remind and direct the reader towards certain actions in accordance with what is desired by the communicator.